Chlamydia exploit the mammalian tryptophan-depletion defense strategy as a counter-defensive cue to trigger a survival state of persistence - Bonner, Carol A.; Byrne, Gerald I.; Jensen, Roy A. (Frontiers in Cellular and Infection Microbiology, 2014)
We previously proposed that in Chlamydiaceae rapid vegetative growth and a quiescent state of survival (persistence) depend upon alternative protein translational profiles dictated by host tryptophan (Trp) availability. These alternative profiles correspond, respectively, with a set of chlamydial proteins having higher-than-predicted contents of Trp (“Up-Trp” selection), or with another set exhibiting lower-than-predicted contents of Trp (“Down-Trp” selection). A comparative evaluation of Chlamydiaceae proteomes for Trp content has now been extended to a number of other taxon families within the Chlamydiales Order. At the Order level, elevated Trp content occurs for transporters of nucleotides, S-adenosylmethionine (SAM), dicarboxylate substrates, and Trp itself. For Trp and nucleotide transporters, this is even more pronounced in other chlamydiae families (Parachlamydiaceae, Waddliaceae, and Simkaniaceae) due to extensive paralog expansion. This suggests that intracellular Trp availability served as an ancient survival cue for enhancement or restraint of chlamydial metabolism in the common Chlamydiales ancestor. The Chlamydiaceae Family further strengthened Up-Trp selection for proteins that function in cell division, lipopolysaccharide biosynthesis, and methyltransferase reactions. Some proteins that exhibit Up-Trp selection are uniquely present in the Chlamydiaceae, e.g., cytotoxin and the paralog families of polymorphic membrane proteins (Pmp's). A striking instance of Down-Trp selection in the Chlamydiaceae is the chorismate biosynthesis pathway and the connecting menaquinone pathway. The newly recognized 1,4-dihydroxy-6-napthoate pathway of menaquinone biosynthesis operates in Chlamydiaceae, whereas the classic 2-napthoate pathway is used in the other Chlamydiales families. Because of the extreme Down-Trp selection, it would appear that menaquinone biosynthesis is particularly important to the integrity of the persistent state maintained under conditions of severe Trp limitation, and may thus be critical for perpetuation of chronic disease states.